The Effect Of Work Environment, Personal Characteristics, Technical Skills, And Experience On The Performance Of Contract Employees at PT. Telkom Akses Lampung - Indah Mutira; Febrianty; Anita (Malaqbi Publisher, 2026)
This study aims to evaluate the effect of Work Environment, Personal Characteristics, Technical Skills, and Work Experience on the job performance of contract technicians at PT. Telkom Akses Lampung. The urgency of this research is based on the need to optimize technical human resources in order to ensure the stability of telecommunication services. The population of this study consisted of 120 contract employees, with the sampling technique using accidental sampling, where respondents were selected based on their availability and suitability as research subjects. This study employed a quantitative approach with Structural Equation Modeling (SEM) analysis using SmartPLS software. The results show that Personal Characteristics, Technical Skills, and Work Experience have a positive and significant effect on employee performance. In contrast, the Work Environment was found to have no significant effect on technician performance in this research model. These findings indicate that individual competence and work experience are the main determinants of field technician performance. In conclusion, improving human resource quality through strengthening skills and work experience is more critical than improving the work environment in this context. The results of this study are expected to provide valuable input for company management in enhancing technician performance.